2009
DOI: 10.1080/15563650903018611
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol intoxication requiring hospital admission in children and adolescents: retrospective analysis at the University Children's Hospital in the Slovak Republic

Abstract: The results of this analysis emphasize the severity of underage alcohol consumption by young people in the Slovak Republic. Measures are needed to decrease alcohol abuse in children and adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 13 publications
6
38
0
2
Order By: Relevance
“…The proportion of children admitted with alcohol intoxication increased every year [14]. Our study showed the mean age of alcohol poisoned patients (mean ± standard deviation) 14.91 ± 1.45 years.…”
Section: Discussionmentioning
confidence: 86%
“…The proportion of children admitted with alcohol intoxication increased every year [14]. Our study showed the mean age of alcohol poisoned patients (mean ± standard deviation) 14.91 ± 1.45 years.…”
Section: Discussionmentioning
confidence: 86%
“…1 Çocukluk çağında alkol zehirlenmelerinin epidemiyolojisini gösteren ça-lışma sayısı da azdır. 2,[11][12][13] Genellikle alkol ve neden olduğu psikososyal sorunlar üzerine yapılan çalış-malar literatürde bulunmaktadır. Bizim çalışma-mızda acil servisimize başvuran 1871 zehirlenme olgusunun %2,3'ünü alkol zehirlenmeleri oluştur-maktaydı.…”
Section: Discussionunclassified
“…Acil servise başvuru anında olguların GKS ortanca değeri 15 (7)(8)(9)(10)(11)(12)(13)(14)(15), ZŞS ortanca değeri 1 (0-3) idi. Sadece 3 (%7,0) olgunun GKS≤8 idi.…”
Section: Bulgularunclassified
“…2 Refers to participants who reported regular alcohol use. 3 According to DSM-IV. 4 Refers to regular smokers.…”
Section: Prevalence Of Substance Use and Use-related Problemsmentioning
confidence: 99%
“…In many European, countries the number of adolescents admitted to in-patient treatment with alcohol intoxication (AIA) has dramatically risen over the last 10 years [1][2][3]. In Germany, this figure increased for individuals between the ages of 10 and 20, from 14,105 cases in 2003 to 26,673 in 2012 [4].…”
Section: Introductionmentioning
confidence: 99%